DETERMINATION OF THE BENEFITS AND COMPLICATIONS OF CLEAN INTERMITTENT CATHETERIZATION TO SPINAL CORD INJURED PATIENTS - Raheem Badr (Global Journal of Public Health Medicine, 2023)
Background: Intermittent catheterization (IC) is the best method for bladder emptying in patients with spinal cord lesions who are suffering from neurogenic bladder dysfunction. This is safe and effective method, leads to improved kidney and upper urinary tract status, lessening of vesicoureteral reflux and improved of continence and reduce urinary tract infection (UTI). In addition, patient quality of life is enhanced by the increased independence and security offered by use self-Intermittent catheterizations (1, 2).